Surgical treatment of multiple sporadic colorectal carcinoma. - Cecchini, Stefano; Azzoni, Cinzia; Bottarelli, Lorena; Marchesi, Federico; Rubichi, Francesco; Silini, Enrico Maria; Roncoroni, Luigi (Acta Biomedica Atenei Parmensis, 2017)
Aim: Many aspects of the surgical management of multiple sporadic colorectal cancer syndrome, either synchronous and metachronous, remain to be cleared, in particular the prognostic influence of the extent of surgical resection. Method: A retrospective review was performed of patients diagnosed with multiple colorectal cancer from 1982 to May 2010. Clinical and pathologic data were collected and reviewed. Survival analysis was performed. Results: We identified 23 patients with multiple sporadic colorectal cancers, of which 8 had synchronous (SC) and 15 metachronous cancers (MC). Of the MC patients, 2 (13%) had the second cancer within 2 years, 4 (27%) in the time period of 2-5 years and 9 (60%) after 5 years. Twenty-one patients underwent multiple segmental resections; 2 patients underwent subtotal colectomy. The 5-year overall survival rate of SC and MC patients was 100% and 87% (p